2020
DOI: 10.1161/jaha.120.018917
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants in Patients With Inherited Thrombophilia and Venous Thromboembolism: A Prospective Cohort Study

Abstract: Background In this prospective cohort study, we aimed to evaluate the efficacy and safety of direct oral anticoagulants (DOACs) versus heparin/vitamin K antagonists for the treatment of venous thromboembolism (VTE) in patients with inherited thrombophilia. Methods and Results We enrolled consecutive patients with acute VTE and inherited thrombophilia treated with DOACs (cases) or heparin/vitamin K antagonists (controls), matched for age, sex, ethnicity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
1
32
1
Order By: Relevance
“…Due to heterogeneity between oral anticoagulant users and non-users in real-world data, some of the baseline comorbidities and concomitant medications (antiplatelets, NSAIDs, and corticosteroids) were not fully balanced with PS matching, and had to be additionally adjusted for by the multiple logistic regression analysis in order to minimize potential confounding effects. Although NOACs have been associated with increased risk of gastrointestinal, gynecological and urological bleeding in other studies, 41 , 42 such risk was not detected in the present study, which might have been affected by the aforementioned deferential comedication patterns between groups. Due to the limited number of NOAC-using cancer patients satisfying the inclusion criteria for study entry, we had to collectively categorize all the patients on any of the NOAC agents as the NOAC group, regardless of prophylactic or treatment doses used.…”
Section: Limitationscontrasting
confidence: 83%
“…Due to heterogeneity between oral anticoagulant users and non-users in real-world data, some of the baseline comorbidities and concomitant medications (antiplatelets, NSAIDs, and corticosteroids) were not fully balanced with PS matching, and had to be additionally adjusted for by the multiple logistic regression analysis in order to minimize potential confounding effects. Although NOACs have been associated with increased risk of gastrointestinal, gynecological and urological bleeding in other studies, 41 , 42 such risk was not detected in the present study, which might have been affected by the aforementioned deferential comedication patterns between groups. Due to the limited number of NOAC-using cancer patients satisfying the inclusion criteria for study entry, we had to collectively categorize all the patients on any of the NOAC agents as the NOAC group, regardless of prophylactic or treatment doses used.…”
Section: Limitationscontrasting
confidence: 83%
“…These trials evidences are supported by data from real world and observational studies, where DOACs have demonstrated significantly lower rates for major bleeding and a positive net clinical benefit compared to VKAs [ 10 13 ]. In VTE patients, the use of DOACs has also been associated with a lower risk of VTE recurrence even after anticoagulant discontinuation [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, data from the first‐ever prospective cohort study focused on DOACs versus heparin and VKA for VTE treatment and secondary prevention in patients with inherited thrombophilia was published by Campello et al 16 In this study including a large cohort of patients with thrombophilia experiencing VTE (n = 597), the DOAC efficacy in preventing VTE recurrence was comparable to that observed with VKA and heparin (cumulative incidence of recurrence during anticoagulation, 1.09% [95% CI, 0.22%‐3.31%] in DOAC‐treated patients versus 1.83% [95% CI, 0.74%–4.3%] in controls). For all recurrent events in the DOAC group (n = 3), precipitating factors could be demonstrated, including insufficient compliance, polycythemia vera, and APS occurrence.…”
Section: Risk Factor Risk Of Ischemic Stroke or Venous Thromboembolicmentioning
confidence: 99%